Development of Integer Number Learning Devices Using Moluccas Local Wisdom - Christina M Laamena; Theresia Laurens (EduMa: Mathematics education learning and teaching, 2021)
An Integer is one material that is still considered difficult by students, even junior and senior high school students. Therefore it is necessary to prepare a learning media that can help students to master integers well.Â  Various media have been developed to make it easier for students to understand and operate integers. However, the media is still far from the reach of students. This study aims to develop learning media for integers based on local Maluku wisdom as well as learning tools, namely the Lesson Plan, teaching materials, and student worksheets that serve as a guide in learning. This research is development research using the ADDIE development model, which consists of stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The research begins by analyzing the students' abilities on integer material and teaching materials and the media used in learning. Then the researcher designed the media and learning tools which were then submitted to the experts to be validated and to students for their implementation. Based on the results of the validation of experts and student learning outcomes, it can be concluded that the resulting learning tools are valid and can be usedÂ